Synthesis, X-ray crystal structures, thermal and electrochemical properties of thiosemicarbazidatodioxouranium(VI) complexes - KOCA, ATIF (ROYAL SOC CHEMISTRY, 2010)
The stable uranyl complexes, [UO2(L)C9H19OH], were obtained from 3,5-dichlorosalicyl-(L-I) and salicyl-aldehyde-S-propyl-thiosemicarbazones (L-II) with substituted-salicylaldehyde in nonyl alcohol. The structures of the complexes have been characterized by elemental analysis, IR, H-1 NMR, conductivity, magnetic moment measurements, cyclic voltammetry, thermal gravimetric analysis and single crystal X-ray diffraction technique. The U(VI) centre is seven-coordinated in a distorted pentagonal bipyramidal geometry. The relative orientations of the nonyl alcohol and S-propyl group in the title complexes are completely different due to different crystal packing. Electrochemical behaviors of the thiosemicarbazone ligands and the uranyl complexes were studied using cyclic voltammetry and square wave voltammetry. Redox processes of the compounds are significantly influenced by the central metal ions and the nature of substituents on the thiosemicarbazones, which are important factors in controlling the redox properties. In situ spectroelectrochemical studies were employed to determine the colors and spectra of electro-generated species of the complexes.
Keywords: NONEQUIVALENT COORDINATION ENVIRONMENTS; BINUCLEATING AROYL HYDRAZONES; NUCLEAR-MAGNETIC-RESONANCE; THIOSEMICARBAZONE COMPLEXES; MOLECULAR-STRUCTURE; METAL-COMPLEXES; DIOXOMOLYBDENUM(VI) COMPLEXES; DIOXOURANIUM COMPLEXES; REDOX PROPERTIES; VIC-DIOXIME